Construction and system evolution analysis of China’s food security indicator system - Yuting, Zhao; Meng, Qu (Frontiers in Sustainable Food Systems, 2024)
In recent years, the number of countries experiencing a deterioration in food security has been increasing to the detriment of the healthy development of their people. China has made significant achievements in safeguarding food security, but only some studies have comprehensively summarized China’s important initiatives and successful experiences in protecting food security since the 1960s. In this paper, we use qualitative and quantitative methods to determine the food security indicator system and observe the development of China’s food security from 1961 to 2019 to provide a reference for countries threatened by hunger and malnutrition to get out of the predicament. First, 199 pieces of literature were subjected to three-level coding and saturation test using Nvivo software to preliminarily establish an indicator system for measuring China’s food security, which consists of two categories: food chain and external environment, five subsystems: food supply, food circulation, food consumption, international factors, and domestic factors, as well as 12 specific indicators. Subsequently, the entropy weight coefficient and hierarchical analysis methods are used to calculate two different indicator weights. Monte Carlo simulation compares the uncertainty of the indicator weights calculated by the two methods. We found that the uncertainty of the indicator weights determined by the hierarchical analysis method is much higher than that of the entropy coefficient method, so the indicator weights determined by the entropy coefficient method are chosen. Based on the formation of the food security indicator system, the obstacle degree test was carried out for each indicator. We found that the average wage of urban employees before 2015 was the main obstacle to China’s food security. However, the population kept growing after 2015, which became the main obstacle to China’s food security. Secondly, the evolution characteristics of the overall level of China’s food security and the subsystems from 1961 to 2019 were analyzed individually. We found that the overall level of China’s food security has been continuously improving. However, the subsystems still have hidden dangers, and the most prominent one is the food consumption subsystem, whose composite index has been continuously decreasing and has become the main factor undermining China’s food security. The scientific construction of China’s food security indicator system will help to identify and warn of hidden food security problems promptly and, at the same time, will help to summarize and promote China’s successful experience in safeguarding food security. Food security is the foundation of agricultural development, and ensuring food security significantly impacts national security, social stability, people’s livelihoods, and health. A scientifically constructed indicator system for China’s food security can help identify and alert potential food security risks. Based on accurate indicator data and analysis results, more effective food security policies and measures can be formulated, ultimately promoting the sustainable development of the gain industry.